Personal Productivity and Well-being - Chapter 2 of the 2021 New Future of Work report - Butler, Jenna; Czerwinski, Mary; Iqbal, Shamsi; Jaffe, Sonia; Nowak, Kate; Peloquin, Emily; Yang, Longqi (The New Future of Work: Research from Microsoft on the Impact of the Pandemic on Work Practices, 2021)
We now turn to understanding the impact that COVID-19 had on the personal productivity and well-being of information workers as their work practices were impacted by remote work. This chapter overviews people's productivity, satisfaction, and work patterns, and shows that the challenges and benefits of remote work are closely linked. Looking forward, the infrastructure surrounding work will need to evolve to help people adapt to the challenges of remote and hybrid work.